أحكام العبادات في ظل الأحوال الجوية: دراسة فقهية لأثر الأحوال الجوية في العبادات - Shebani, Hassan Maoloud; Mohd Izhar Ariff Mohd Kashim; Mohammad Zaini Yahya (Department of Theology and Philosophy, Faculty of Islamic Studies, Universiti Kebangsaan Malaysia, 2016)
The article aims to examine the extent of compatibility between acts of worship and their weather conditions to avoid either missing or breaching them. It discusses some weather circumstances that may hinder the performance of the obligatory acts of worship properly. While the the worshipper performing his duty towards his Lord in certain unusual natural circumstances, may be forced to change how performing worship. For instance, ablution for non-excused due to cold weather and absence of hot water, is it permissible in this case to take tayammum instead of ablution? Another instance, due to either heavy rain or too cold during Hajj season, can the pilgrim omit or delay some rites? Significance of this article is due to the importance of such cases and developments of this era in the weather circumstances context that relates to the acts of worships. The article investigates the impacts of weather circumstances on the provisions of the acts of worship.